Biocatalytic Self‐Assembly of Nanostructured Peptide Microparticles using Droplet Microfluidics. Issue 2 (5th August 2013) - Bai, Shuo; Debnath, Sisir; Gibson, Kirsty; Schlicht, Barbara; Bayne, Lauren; Zagnoni, Michele; Ulijn, Rein V.
<x xml:space="preserve">Abstract</x> Uniformly‐sized, nanostructured peptide microparticles are generated by exploiting the ability of enzymes to serve (i) as catalysts, to control self‐assembly within monodisperse, surfactant‐stabilized water‐in‐oil microdroplets, and (ii) as destabilizers of emulsion interfaces, to enable facile transfer of the produced microparticles to water. This approach combines the advantages of biocatalytic self‐assembly with the compartmentalization properties enabled by droplet microfluidics. Firstly, using microfluidic techniques, precursors of self‐assembling peptide derivatives and enzymes are mixed in the microdroplets which upon catalytic conversion undergo molecular self‐assembly into peptide particles, depending on the chemical nature of the precursors. Due to their amphiphilic nature, enzymes adsorb at the water‐surfactant‐oil interface of the droplets, inducing the transfer of peptide microparticles from the oil to the aqueous phase. Ultimately, through washing steps, enzymes can be removed from the microparticles which results in uniformely‐sized particles composed of nanostructured aromatic peptide amphiphiles.